An Investigation into Using Peer Feedback in Project based Learning for Eighth Graders in Danang Lower Secondary Schools - Nguyễn Lê Như Quỳnh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to (i) investigate the application of peer feedback in project-based learning of the grade 8 students of secondary schools in Da Nang city (ii) identify difficulties while using peer feedback in team projects for the eighth grade students of secondary schools in Da Nang city